Peningkatan Pertumbuhan Serta Hasil Panen Jagung Dengan Mengimplementasikan Jarak Dan Kedalaman Tanam Bersama Wanita Tani Desa Air Duren - Holidah Holidah; Rahmatiyah Rahmatiyah (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2025)
In Indonesia, maize has replaced rice as the staple food. However, many farmers fail to achieve optimal maize growth rates and yields because the maize planting techniques developed by them depend only on their knowledge and understanding of the relevant sciences relevant to maize planting. To determine the effect of applying different spacing and planting depths on the growth and yield of maize was the objective of this study. A factorial RAK model with two factors was used in this study. There were three levels of planting distance notation (J) in this RAK: 70 x 25 cm for Planting Distance 1, 70 x 40 cm for Planting Distance 2, and 75 x 50 cm for Planting Distance 3. There were also four levels of planting depth notation (K): 3 cm for Depth 1, 5 cm for Depth 2, 7 cm for Depth 3, and 8 cm for Depth 4. The results showed that it could really affect the growth and yield of corn at the correlation of spacing 75 x 50 cm and depth 5 cm. Farm women also contribute to this activity with their experience and skills because the higher the presence of farm women who contribute will make the results of corn farming higher.